Формула невимірності у сербській та чорногорській народній поезії - Микитенко, О. (Народна творчість та етнографія, 2005)
The conceptual metaphor is researched in this article on the material of funeral lament, which is caused by a wide discussion of the theme of death as an object of cultural anthropology nowadays. The author studies ethnopoetic constant textual models of Slavonic culture, Serbian and Montenegrin in particular. The concepts, oppositions and epic picture of the world of the researched culture, the techniques of the genre are investigated.